Rabies Elimination: Is It Feasible without Considering Wildlife?. (26th June 2022) - Acharya, Krishna Prasad; Chand, Rakesh; Huettmann, Falk; Ghimire, Tirth Raj
Abstract : Rabies is a vaccine-preventable fatal viral disease that is zoonotic in nature. In this article, we provide a justification why the agreement of the World Health Organization (WHO), the Food and Agriculture Organization (FAO), the World Organization for Animal Health (OIE), and Global Alliance for Rabies Control (GARC) on The Global Strategic Plan to End Human Deaths from Dog-mediated Rabies by 2030 should also include a more holistic approach and ecologic views.